Enhancing the Total Terminal Galactosylation of CHO Cell-Derived TNF-α Blocker-IgG1 Monoclonal Antibody Using Time-Dependent Galactose Supplementation - Mallikarjuna Pulipeta; Pradeep Kumar Iyer; Rajendra Kumar Palakurthy; Narasimha Pullaguri; Rajasekhar Pinnamaneni; Srinivas Reddy Chilukuri (Biologics)
Background: Recombinant monoclonal antibodies represent a vital category of biologics, constituting the largest class of molecules used to treat autoimmune disorders, cancers, rheumatoid arthritis, and other chronic conditions. The IgG1 subclass is the most potent among all the immunoglobulin gamma (IgG) antibodies, inducing Fc-related effector functions. N-linked glycan distribution of therapeutic IgG1s affects Fc-related effector functions such as CDC (complement-dependent cytotoxicity) and ADCC (antibody dependent cell-mediated cytotoxicity) biological activities and efficacy in vivo. Hence, as a critical quality attribute (CQA), the glycosylation profile of therapeutic IgG1s must be consistently preserved, which is primarily influenced by manufacturing process factors. In the era of biosimilars, it is challenging for biopharmaceutical manufacturers to not only obtain the desired glycan distribution consistently but also to meet the innovator molecule specifications as per the regulatory agencies. Methods: This study investigates the CHO fed-batch process parameters that affect the titer and terminal galactosylation of the TNF-α blocker-IgG1. It was hypothesized that galactose supplementation would enhance the galactosylation of TNF-α blocker-IgG1. Results: It was observed that such in-cultivation process shift does not affect cell culture parameters yet significantly enhances the galactosylation of TNF-α blocker-IgG1. Interestingly, the results indicate that supplementing D-galactose from the exponential phase of the CHO fed-batch process had the greatest effect on Fc galactosylation, increasing the amount of total galactosylated TNF-α blocker-IgG1 from 7.7% to 15.8%. Conclusions: Our results demonstrate a relatively easy and viable technique for cell culture engineering that is more appropriate for industrial production than costly in vitro glycoengineering.